2013
DOI: 10.1093/icvts/ivt299
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seasons and lunar cycle on hospital outcomes following ascending aortic dissection repair

Abstract: Season had no effect on mortality or LOS following aortic dissection repair, while patient age significantly increased the odds of death. The full-moon cycle appeared to reduce the odds of death, and the full-moon cycle, along with being male and requiring a concomitant cardiac procedure, was associated with shorter LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The analysis also found a significant increase in relative risk on Monday, and in the morning from 6 am to noon. As with Shuhaiber [12] the weekly and circadian variation was not easily explainable but serves to emphasize that such variations can be observed.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The analysis also found a significant increase in relative risk on Monday, and in the morning from 6 am to noon. As with Shuhaiber [12] the weekly and circadian variation was not easily explainable but serves to emphasize that such variations can be observed.…”
Section: Resultsmentioning
confidence: 87%
“…Other chronobiological themes have been examined in STADs. Recently, Shuhaiber et al [12] examined the impact of the lunar cycle on mortality and length of stay following surgical repair of STAD. Season did not have a significant impact on survival, but the lunar cycle, specifically the Full moon, impacted the data in six month blocks, the mirror image results are strikingly seen (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective investigation of 15,985 patients with acute myocardial infarction, Wende et al observed a possible cardioprotective time of three days after a new moon [ 17 ]. The odds of death were reduced at full moon in 210 patients who had undergone repair for dissection in the ascending aorta [ 18 ]. A significantly higher number of admissions were noted at full moon in 7219 patients with medically unexplained acute stroke symptoms [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were diagnosed by specialist cardiologist and they detected that AMI occurs during resting position or bed rest position. Another study tried to identify the effects of the lunar cycle and seasonal variation on ascending aortic dissection surgery outcomes [14] they also applied these factors on risk adjusted hospital mortality and the length of stay followed by surgery for survivors. They chose different criteria for their investigation like first they want to co-relate full moon and seasonal variation, demographic and patient risk varieties and made a model that controls demographic risk factor of people like age, different kind of diseases (diabetes mellitus, hypertension).…”
Section: Effect Of Full Moon On Different Aspects Of Human Healthmentioning
confidence: 99%